Ministry in the Highland Countries: Lay Readership and Ordained Ministry in the Swiss Reformed Church and the Church of Scotland - Stephany, André M. (Studia liturgica, 2025)
The Swiss Reformed Church has very diverse understandings of lay readership and ordained ministry depending on the geographic region. While many cantonal churches are continually developing their ministry of lay readers, the question regarding how this non-stipendiary office relates to stipendiary ordained ministry is still an open one. This article describes the diversity of this ministry in Switzerland and then compares the Swiss approach with the approach the Presbyterian Church of Scotland has chosen. It argues that a broader understanding of ordained ministry that also includes alternative paths of training and non-stipendiary or bi-vocational concepts is able to better acknowledge the wide variety of vocations to the ministry of the word and would sharpen the profiles of each of these recognized ministries. This comparison may be of interest for other denominations as well, since a changing world challenges the traditional privileges of the ordained orders across the churches. The relationship of ordained and lay ministry and the question of which ministries should or should not be ordained urges the churches to think about the core of the ordained ministry of word and sacrament. This article shows how two churches are striving for an understanding of ministry that serves the church of the future.